The Predictors of Post-Procedural Arm Pain after Transradial Approach in 1706 Patients Underwent Transradial Catheterization - Dharma, Surya; Kedev Sasko; Patel, Tejas; Gilchrist, Ian C; Rao, Sunil V (Elsevier BV, 2019)
Although patients prefer radial over femoral approach, some develop post-procedural arm pain after transradial procedures. This complication has been poorly defined in prior studies. We evaluated the extent of non-ischemic arm pain after transradial arterial access and identify variables that may be associated with this complication.